Ultrasensitive determination of 5-methylcytosine and 5-hydroxymethylcytosine in genomic DNA by sheathless interfaced capillary electrophoresis–mass spectrometry. Issue 13 (12th January 2016) - Yuan, Fang; Zhang, Xiao-Hui; Nie, Ji; Chen, Hong-Xu; Zhou, Ying-Lin; Zhang, Xin-Xiang
Abstract : An ultrasensitive sheathless capillary electrophoresis–electrospray ionization–mass spectrometry system is developed for the determination of 5′-mdC and 5′-hmdC in only 125 pg (∼20 cells) genomic DNA samples. Abstract : A newly developed sheathless interface for capillary electrophoresis–mass spectrometry, using a porous tip sprayer, was first applied for highly sensitive determination of cytosine modifications. The system performed well in identification and quantification of both 5-methylcytosine and 5-hydroxymethylcytosine using only 125 pg (∼20 cells) genomic DNA samples.